(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2018)
The highland of Bale is known with potato production, but post harvest quality of the crop is not emphasized yet. Therefore, this study was conducted to evaluate six potato varieties with the objective of assessing the effect of varieties and growing on tuber nutritional and process quality of potato grown in Sinana and Dinsho highlands of Bale. The experiment was laid out in randomized complete block design with three replications. The varieties showed highly significant (P<0.05) differences for all the parameters studied across the locations. The highest specific gravity, dry matter content and starch content (1.107, 26.61 and 19.19) were recorded from Dinsho location for Guddene variety while the lowest specific gravity, dry matter content and starch content (1.084, 19.41 and 14.61) were recorded from Sinana location for Ararsa variety. Most of the varieties were recorded as the highest values of specific gravity, dry matter and starch content at Dinsho indicating that it is an ideal location for potato production to be used for processing while Sinana is suitable for the production for home consumption. However, it is necessary to evaluate these varieties for a number of seasons and locations to recommend with high post harvest quality parameters required by the processors. Int. J. Agril. Res. Innov. & Tech. 7 (2): 18-21, December, 2017